2008
DOI: 10.1212/01.wnl.0000314649.38527.93
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex stimulation for chronic pain

Abstract: This meta-analysis shows that two different techniques of brain stimulation of motor cortex--invasive and noninvasive--can exert a significant effect on pain in patients with chronic pain. We discuss potential reasons that invasive brain stimulation showed a larger effect in this meta-analysis. Our findings encourage continuation of research in this area and highlight the need for well-designed clinical trials to define the role of brain stimulation in pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(131 citation statements)
references
References 50 publications
3
123
0
3
Order By: Relevance
“…70 Over the past decade, several studies have shown that rTMS applied over the motor cortex can also, at least temporarily, alleviate neuropathic pain. [71][72][73][74] To date, about 20 studies have assessed the efficacy of rTMS in more than 300 persons with drugresistant chronic neuropathic pain of diverse origins (including post-stroke pain, CRPS, trigeminal neuralgia, amputation, spinal-cord injury, and brachial plexus avulsion), 74 and recent meta-analyses showed that highfrequency rTMS is associated with significant pain relief. 72,73 Does the reduction in pain following stimulation of the motor cortex indicate that motor-cortex plasticity is a cause of chronic neuropathic pain?…”
Section: Can the Induction Of Motor Plasticity By Means Of Motor-cortmentioning
confidence: 99%
“…70 Over the past decade, several studies have shown that rTMS applied over the motor cortex can also, at least temporarily, alleviate neuropathic pain. [71][72][73][74] To date, about 20 studies have assessed the efficacy of rTMS in more than 300 persons with drugresistant chronic neuropathic pain of diverse origins (including post-stroke pain, CRPS, trigeminal neuralgia, amputation, spinal-cord injury, and brachial plexus avulsion), 74 and recent meta-analyses showed that highfrequency rTMS is associated with significant pain relief. 72,73 Does the reduction in pain following stimulation of the motor cortex indicate that motor-cortex plasticity is a cause of chronic neuropathic pain?…”
Section: Can the Induction Of Motor Plasticity By Means Of Motor-cortmentioning
confidence: 99%
“…It has been proposed that the cortex may reduce pain by interrupting the transmission of noxious information from the spinal cord level by activating descending pain modulatory systems located in the brainstem [6] . Recent studies have shown that the anterior cingulate cortex (ACC), the insular cortex, the primary (SI) and secondary (SII) somatosensory cortices, the ventrolateral orbital cortex (VLO) and the motor cortex are involved in pain modulation [3][4][5][7][8][9][10][11] . These cortical structures constitute, respectively, the medial and lateral pain systems, the nucleus submedius (Sm)-VLO-periaqueductal gray (PAG) system and the motor cortex system [3][4][5][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the anterior cingulate cortex (ACC), the insular cortex, the primary (SI) and secondary (SII) somatosensory cortices, the ventrolateral orbital cortex (VLO) and the motor cortex are involved in pain modulation [3][4][5][7][8][9][10][11] . These cortical structures constitute, respectively, the medial and lateral pain systems, the nucleus submedius (Sm)-VLO-periaqueductal gray (PAG) system and the motor cortex system [3][4][5][7][8][9][10][11] . Multiple neurotransmitters, including opioid, glutamate, GABA and dopamine transmitters, are involved in the modulation of pain by these cortical structures [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are few reports about CRPS patients treated with this technique though it seems to have significant effect on CRPS pain [47-50] and superior weighted responder rate than non-invasive techniques [51]. Even though MCS has high cost and higher complication rates (as well as other invasive stimulation technics), at this time it is more commonly employed than DBS, since it is more easily carried out and it has a large spectrum of indications [52].…”
Section: Motor Cortex Stimulation (Mcs)mentioning
confidence: 99%